Coupled modes of North Atlantic Ocean-atmosphere variability and the onset of the Little Ice Age - Anchukaitis, Kevin J.; Cook, Edward R.; Cook, Benjamin I.; Pearl, Jessie K.; D'Arrigo, Rosanne; Wilson, Rob (Geophysical Research Letters, 2020)
This research was funded by grants from the US National Science Foundation P2C2 program (AGS-1501856, and AGS-1502224). BIC was supported by the NASA Modeling, Analysis, and Prediction program (NASA #80NSSC17K0265). Hydroclimate extremes in North America, Europe, and the Mediterranean are linked to ocean and atmospheric circulation anomalies in the Atlantic, but the limited length of the instrumental record prevents complete identification and characterization of these patterns of covariability especially at decadal to centennial timescales. Here we analyze the coupled patterns of drought variability on either side of the North Atlantic Ocean basin using independent climate field reconstructions spanning the last millennium in order to detect and attribute epochs of coherent basin-wide moisture anomalies to ocean and atmosphere processes. A leading mode of broad-scale moisture variability is characterized by distinct patterns of North Atlantic atmosphere circulation and sea surface temperatures. We infer a negative phase of the North Atlantic Oscillation and colder Atlantic sea surface temperatures in the middle of the 15th century, coincident with weaker solar irradiance and prior to strong volcanic forcing associated with the early Little Ice Age. Peer reviewed